1992
DOI: 10.1084/jem.176.2.427
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence and origin of somatically mutated memory B cells in mice.

Abstract: SummaryWhile most murine peripheral B cells express germline-encoded antibodies of classes M and D (# +/~ + cells), small numbers of memory B cells expressing somatically mutated immunoglobulin G antibodies are generated upon T cell-dependent immunization. Analyzing the antibody repertoire of the #-~-B cell pool in unimmunized mice, we show that these cells express somatically mutated V. genes and that most of these genes derive from a set of germline V. genes dominantly expressed by #+8 + B cells. Thus, class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 51 publications
3
55
0
Order By: Relevance
“…Both subtypes are GC derived (35,36) and mediate host protection for a long period of time. In addition, there exist surface IgM + memory B cells exhibiting hypermutated BCRs that also persist over extended periods of time (11,12). Recently, it has been shown that these latter memory B cells constitute a proliferationcompetent pool of memory B cells that may differentiate into IgG + memory B cells upon antigenic challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both subtypes are GC derived (35,36) and mediate host protection for a long period of time. In addition, there exist surface IgM + memory B cells exhibiting hypermutated BCRs that also persist over extended periods of time (11,12). Recently, it has been shown that these latter memory B cells constitute a proliferationcompetent pool of memory B cells that may differentiate into IgG + memory B cells upon antigenic challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, memory B cells express isotype-switched IgG or IgA Igs on their surface. However, immunization with protein or polysaccharide Ags can also result in a pool of IgM + memory B cells (11)(12)(13)(14)(15). Memory B cells appear to efficiently recirculate throughout the lymphatic system and are found at comparable frequencies in all lymphoid organs as well as in the blood (16).…”
mentioning
confidence: 99%
“…Nucleotides in codons 31 II , 38 III , 65 II , 100 II , 100 AII and III and 105 II (numbering according to Kabat & Wu 1991) have been described as mutational hot spots of the V H B1-8 gene (Fukita et al 1998;Schittek & Rajewsky 1992;Weiss & Rajewsky 1990). From a total of 52 breaks, two breaks occurred 5' of 38 III , ¢ve breaks 5' of 65 II and one break 5' of 100A III .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown in the murine system that slgD*" cells from adults show preferential expression of certain VH genes, indicating that they have already encountered environmental antigens and passed through a certain selection process in vivo [39,40]. It is also reported that sIgD'*' fraction from adult mouse contains antigen-specific memory B cells [41].…”
Section: Iga-and Iga2-producing Cells Induced In Neonatal and Adult Bmentioning
confidence: 99%